2017
DOI: 10.1002/adma.201604634
|View full text |Cite
|
Sign up to set email alerts
|

Degradability and Clearance of Silicon, Organosilica, Silsesquioxane, Silica Mixed Oxide, and Mesoporous Silica Nanoparticles

Abstract: The biorelated degradability and clearance of siliceous nanomaterials have been questioned worldwide, since they are crucial prerequisites for the successful translation in clinics. Typically, the degradability and biocompatibility of mesoporous silica nanoparticles (MSNs) have been an ongoing discussion in research circles. The reason for such a concern is that approved pharmaceutical products must not accumulate in the human body, to prevent severe and unpredictable side-effects. Here, the biorelated degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
498
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 633 publications
(539 citation statements)
references
References 502 publications
9
498
0
3
Order By: Relevance
“…Though tremendous effort has been expended to use MSNs in immunotherapies, a lingering concern of silica nanoparticles is their poor degradability, accumulation, and potential toxicity. To abate these concerns, Khashab and co‐workers recently published an expansive review that covers the mechanisms driving degradation and the effect of dosages, material subtypes, and physical characteristics (e.g., particle shape, size, pore size, coating, and concentration) on degradation and clearance of MSNs that may pave a way to advance these materials into clinical practice as a material for immunotherapy …”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…Though tremendous effort has been expended to use MSNs in immunotherapies, a lingering concern of silica nanoparticles is their poor degradability, accumulation, and potential toxicity. To abate these concerns, Khashab and co‐workers recently published an expansive review that covers the mechanisms driving degradation and the effect of dosages, material subtypes, and physical characteristics (e.g., particle shape, size, pore size, coating, and concentration) on degradation and clearance of MSNs that may pave a way to advance these materials into clinical practice as a material for immunotherapy …”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…These nanoparticles are prepared from polytrialkoxysilylated organic precursors, which are condensed in mild conditions using the sol‐gel procedure, without the presence of any silica source. Recent studies have shown the excellent biocompatibility of these nanoparticles . Of interest are their porous analogues, which have also been reviewed and are particularly suitable for theranostic applications and drug delivery .…”
Section: Introductionmentioning
confidence: 99%
“…Silica‐based NP is hydrolytically unstable and is gradually converted to silicic acid or polysilicic acid, which are nontoxic and can safely be excreted/absorbed by the human body . Moreover, today it is possible to design highly biodegradable MS NPs .…”
Section: Mesoporous Silica Nanostructuresmentioning
confidence: 99%
“…Apart from the mentioned PCPs, surfactant removal method can also have significant impact on biodegradation of MS NPs . Similar to other biosafety parameters discussed above, excretion of MS NPs is highly dependent on their PCPs …”
Section: Mesoporous Silica Nanostructuresmentioning
confidence: 99%